101 nights on the discourse of self-legitimization: the case of Duško Tadić - Da Silva, Miguel Jesus Neves Ferreira; Vidal Bouzon, A.J. (2011)
This thesis addresses the legitimacy discourse of the ad-hoc International Criminal Tribunal for the Former Yugoslavia, by focusing on a particular case study: the Interlocutory Motion challenging the jurisdiction of the Tribunal in the Dusko Tadi6 case. This, the first ever International Criminal Tribunal established by the United Nations Security Council, faced in the initial proceedings with the first indictee to be present in the Chambers a challenge as to the lawfulness of its own establishment, and therefore as to its legitimacy. The lack of historical precedents for this novel jurisdiction, and the context of the more multicultural-driven international relations of the 1990s, that is, because of the collapse of the superpowers and the temporary suspension of the logic of a bipolar world, were all expected to validate a complex discourse of legitimacy, namely, through recourse to extra-legal references. In fact, the acceptance, and therefore the legitimacy, of the new jurisdiction depended on the recognition of a shared historical, cultural and political context, or, at least, of recognizable politicocultural references beyond the legalistic self-contained judicial speech. After extensively reviewing the initial materials of the challenge presented before the court, the thesis focuses its research on the Tribunal's Decisions, both at Trial and Appeal levels, identifying the attempts to break a self-referential legal discourse. The uncertainty of the historical moment, together with the hesitation on the use of politico-cultural references on the part of the Tribunal, sustains the conclusion of this thesis that no coherent legitimacy discourse is here attained.